2022
DOI: 10.3390/ma15030800
|View full text |Cite
|
Sign up to set email alerts
|

Poly-Lysine Dendritic Nanocarrier to Target Epidermal Growth Factor Receptor Overexpressed Breast Cancer for Methotrexate Delivery

Abstract: A fourth generation poly-lysine dendritic nanocarrier (P4LDN)-based targeted chemotherapy for breast cancer is attempted by incorporating an epidermal growth factor receptor (EGFR)-specific short peptide E2 (ARSHVGYTGAR) and the drug methotrexate (MTX) into a nanocarrier system. The drug is incorporated into the nanocarrier using a cathepsin B cleavable spacer: glycine–phenylalanine–leucine–glycine (GFLG). The in vitro analysis of the time-dependent drug release, binding and internalization ability, and the cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…The efficacy analysis using NOD-SCID mice also demonstrated that the DDS reduced tumor volume. The mice treated with the DDSs developed gained weight faster than those treated with the free drug, which allowed for a conclusion that dendrimer is more tolerated by mice than the free drug [129].…”
Section: Dendritic Polymersmentioning
confidence: 99%
“…The efficacy analysis using NOD-SCID mice also demonstrated that the DDS reduced tumor volume. The mice treated with the DDSs developed gained weight faster than those treated with the free drug, which allowed for a conclusion that dendrimer is more tolerated by mice than the free drug [129].…”
Section: Dendritic Polymersmentioning
confidence: 99%
“…A dendrimer can be built on virtually any form of chemistry, and the nature of that chemistry greatly influences its solubility, degradability, and biological activity [ 159 ]. Polyamidoamines (PAMAM) [ 160 ], poly- l -lysine (PLL) [ 161 ], polyamides (polypeptides) [ 162 ], poly (propylene imine) [ 163 ], and carbohydrates [ 164 ] are some of the most frequently used forms of dendrimers in biological applications. However, PAMAM dendrimers are the most prevalent dendrimer scaffold, commercially available with a wide range of generations and surface properties.…”
Section: Types Of Nanocarriersmentioning
confidence: 99%
“…MTX was linked to the nanocarrier by using cathepsin B cleavable spacer (glycine-phenylalanine-leucine-glycine (GFLG)). The results showed that MTX released from the nanosystem decreased the percentage of cells in the G2/M phase and enhanced the percentage of cells in the S and G0 phase in both MDA-MB-231 (EGFR overexpressed) and SiHa (EGFR negative) cells (Narayanan et al, 2022).…”
Section: Stimuli-responsive Polymeric Nanoparticlesmentioning
confidence: 99%